Some aspects of the legal and democratic principles of the activities of co-owners of apartment buildings in the context of development laws - Milova, Tetyana; Danylkiv, Dmytro (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article examines the activities of associations of co-owners of apartment buildings in the context of the development of democratic and legal foundations of the state and society, in particular, the community of co-owners of condominiums, based on such laws of development as the transition of quantitative changes to qualitative changes, unity and struggle of opposites, denial of denial in within certain categories of development. Certain aspects of the impact of the legal support of the activities of associations of co-owners of apartment buildings on the formation of democratic relations from the standpoint of the laws of the development of nature and society have been revealed, based on which democratic shifts in the activities of associations of co-owners of apartment buildings have been specified and the necessity of reforming the housing and communal economy in terms of creating associations of co-owners of multi-apartment buildings as an objectively necessary reality. It has been proven that the growth in the number of created associations of co-owners of apartment buildings is closely related to the corresponding changes in the current legislation, which is an obvious proof of the transition of the number of changes in laws to the quality of these laws, and then to the number of created associations of co-owners of apartment buildings. Attention is drawn to the fact that qualitative changes in the process of creation and activity of associations of co-owners of apartment buildings no longer act as a struggle between the new and the old, or as a unity and struggle of opposites, this is another segment of development, namely the denial of denial. The essence of the law of objection regarding the development of associations of co-owners of apartment buildings consists in reflecting the stages of internal development of the association of co-owners of apartment buildings, improving its functioning in time and space, that is, in long-term existence and in the conditions of market relations. Attention is drawn to the connection between democratic changes and social protection of the population. Provision of social needs is a unifying factor between freedom and necessity and reliable protection of the development of the democratic foundations of society, including the community - the association of co-owners of apartment buildings.